Unstable association in vitro between donor and recipient DNA in Bacillus subtilis. - Van Randen, J (1982)
In addition to stable donor-recipient DNA complexes, unstable complexes between donor and recipient DNA were formed in vitro with Bacillus subtilis. Whereas the stable complexes survived CsCl gradient centrifugation at pH 11.2 and phenol plus sodium p-aminosalicylate extraction with 0.17 M NaCl, the unstable complexes dissociated during these manipulations. The donor moiety from the unstable complexes remained associated with the recipient DNA during phenol plus sodium p-aminosalicylate treatment at 0.85 M NaCl. The unstable complexes could be stabilized artificially by cross-linking with 4,5',8-trimethylpsoralen. Dissociation of the complexes during CsCl gradient centrifugation could be prevented by centrifuging at pH 10. Heterologous DNA fragments derived from phage H1 DNA appeared to be unable to form complexes with the recipient B. subtilis DNA. Unstable complexes were also formed with Escherichia coli DNA, although under all conditions tested, more complex was detectable by using homologous B. subtilis DNA.